Comparative Transcriptome Analysis Reveals Candidate Genes Involved in Isoquinoline Alkaloid Biosynthesis in Stephania tetrandra - Zhang, Yangyang; Kang, Yun; Xie, Hui; Wang, Yaqin; Li, Yaoting; Huang, Jianming (Planta Medica, 2020)
The roots of Stephania tetrandra are used as a traditional Chinese medicine. Isoquinoline alkaloids are considered to be the most important and effective components in this herb, but little is known about the molecular mechanism underlying their biosynthesis. In this context, this study aimed to reveal candidate genes related to isoquinoline alkaloid biosynthesis in S. tetrandra. Determination of tetrandrine and fangchinoline in the roots and leaves of S. tetrandra by HPLC showed that the roots had much higher contents of the two isoquinoline alkaloids than the leaves. Thus, a comparative transcriptome analysis of the two tissues was performed to uncover candidate genes involved in isoquinoline alkaloid biosynthesis. A total of 71 674 unigenes was obtained and 31 994 of these were assigned putative functions based on BLAST searches against 6 annotation databases. Among the 79 isoquinoline alkaloid-related unigenes, 51 were differentially expressed, with 42 and 9 genes upregulated and downregulated, respectively, when the roots were compared with the leaves. The upregulated differentially expressed genes were consistent with isoquinoline alkaloid accumulation in roots and thus were deemed key candidate genes for isoquinoline alkaloid biosynthesis in the roots. Moreover, the expression profiles of 10 isoquinoline alkaloid-related differentially expressed genes between roots and leaves were validated by quantitative real-time polymerase chain reaction, which indicated that our transcriptome and gene expression profiles were reliable. This study not only provides a valuable genomic resource for S. tetrandra but also proposes candidate genes involved in isoquinoline alkaloid biosynthesis and transcription factors related to the regulation of isoquinoline alkaloid biosynthesis. The results lay a foundation for further studies on isoquinoline alkaloid biosynthesis in this medicinal plant.
Keywords: Menispermaceae; Stephania tetrandra; transcriptome; isoquinoline alkaloids; biosynthesis; RT-qPCR